The Role of Environmental Policy as a Moderator in the Influence of Green Innovation and Capital Structure on Firm Value - Agus Pandu Bastian; Ni Luh Anik Puspa Ningsih; Ida Ayu Surasmi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the impact of green innovation and capital structure on firm value and to examine the role of environmental policy in moderating this relationship. The study is motivated by the importance of enhancing firm value through sustainability strategies and effective financing decisions within the energy sector. A quantitative approach with a causal design was employed. The study population consists of energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period, with a sample of 42 companies selected via purposive sampling. Data analysis was conducted using panel data regression with the Random Effect Model (REM) approach. The results indicate that green innovation has a positive and significant effect on firm value, suggesting that increased eco-friendly innovation can enhance a firm's value. Capital structure also exerts a positive and significant influence on firm value, demonstrating that optimal capital structure management can increase market appreciation. Moderation analysis reveals that environmental policy does not moderate the impact of green innovation on firm value; conversely, environmental policy is shown to strengthen the impact of capital structure on firm value. This study contributes to the development of Signaling Theory, the Resource-Based View, and Pecking Order Theory by demonstrating that the effectiveness of environmental policy as a moderating variable depends on the context of the relationship being tested. Practical implications highlight the importance of implementing green innovation, managing capital structure optimally, and effectively applying environmental policies to enhance firm value.